The association between malnutrition, depression and cognitive decline in free-living elderly people in Cyprus: a cross-sectional study - Maria Kantilafti; Andria Hadjikou; Stavri Chrysostomou (BMC Public Health)
Abstract Background Malnutrition, depression, and cognitive decline are significant concerns among the elderly population, yet the relationship between these factors remains underexplored, particularly in Cyprus. This study aimed to assess the prevalence of malnutrition, depression, and cognitive decline in free-living elderly people in Cyprus and to explore the associations between these conditions and various anthropometric, social, and dietary factors. Methods A cross-sectional study was conducted with 248 participants aged ≥ 60 years, using convenience sampling. Data collection included sociodemographic information, anthropometric measurements, and assessments of nutritional status, depression, and cognitive decline using validated tools. Statistical analyses included logistic and linear regression models to evaluate the associations between the variables. Results The study found that 25% of participants were at risk of undernutrition, while 3% were malnourished. Depression was present in 18.6% of the sample, with females showing higher rates than males. Cognitive decline was reported by 42.7% of participants, with a higher prevalence in males. Eating alone was significantly associated with higher risks of both depression (AOR: 2.00) and cognitive decline (β: 0.15), while participation in social activities reduced the risk of depression (AOR: 0.32). Higher muscle mass was associated with a lower risk of cognitive decline (AOR: 0.92). Conclusions Malnutrition, depression, and cognitive decline are interrelated conditions in the elderly population of Cyprus. Social participation and eating with others appear to have protective effects against depression, while maintaining muscle mass may help reduce the risk of cognitive decline. Public health interventions should focus on improving nutritional status and encouraging social engagement among the elderly to protect their mental health.